The Improving Rural Cancer Outcomes Trial: a cluster-randomised controlled trial of a complex intervention to reduce time to diagnosis in rural cancer patients in Western Australia - Correction - Emery, J.; Gray, V.; Walter, F.; Cheetham, Shelley; Croager, E.; Slevin, T.; Saunders, C.; Threlfall, T.; Auret, K.; Nowak, A.; Geelhoed, E.; Bulsara, M.; et al. (Nature Publishing Group, 2018)
This corrects the article DOI: 10.1038/bjc.2017.310.